Contract Law in Practice in Indonesia: A Theoretical Study and its Implementation in Civil Contracts - Richard Richard (Jurnal Pembaharuan Hukum, 2025)
This study aims to analyze the legal position of contracts in civil agreement practices in Indonesia, with a focus on the normative basis in the Civil Code, relevant basic principles, and obstacles that arise in its application. Indonesian contract law relies on the Civil Code, but social, economic, and technological changes necessitate reform to address societal dynamics. The research method used is normative juridical with a doctrinal and conceptual approach. Data was obtained through a literature study of legislation, legal literature, and analysis of research results in legal journals. This approach was used to systematically examine the applicable legal rules, legal principles, and doctrines, as well as their implementation in civil contract practice. The results of the study show that fundamental principles, such as freedom of contract, consensualism, pacta sunt servanda, good faith, and the principle of personality, remain relevant as guidelines in the formation and execution of contracts. However, obstacles still arise from both normative and practical aspects, such as the ambiguity of electronic contract regulations, the use of standard contracts that are detrimental to certain parties, and the public's weak understanding of rights and obligations in contracts.